(untitled) (Al-Mansour Journal, 2022)
Since the rise of the Internet, one of the most important factors of information technology and communication is the security of information. Cryptography was created as a technique for securing the secrecy of communication and many different methods have been developed to encrypt and decrypt data in order to keep the message secret. Unfortunately it is sometimes not enough to keep the contents of a message secret, it may also be necessary to keep the existence of the message secret. The technique used to implement this is called Steganography. In this paper, a combination of cryptography technique and steganography has been proposed. The proposed algorithm encrypts the information before hiding it in image file to increase the complexity of encryption/decryption process. The peak signal-to-noise ratio (PSNR) is obtained 53.5266. The simulation results show the difference between the original image and the stego image will be hardly noticeable to the human eye. The proposed algorithm is implemented in MATLAB (R2013a) program for computer simulations.